Guidelines for sustainable refurbishment of residential buildings - Pires, Carla Malta (2012)
This paper gives an overview of the objectives in a research project currently under development, which is intended to provide a guideline for the sustainable refurbishment of existing residential buildings. It is based on the adaptation of the criteria defined in the methodology of evaluation and certification of sustainability of buildings: SBToolPT. Aiming to develop a guideline on sustainable refurbishment, the present research project investigates two different cases, in order to find out how the refurbishment is done and which possibilities and barriers there are to achieve a sustainable refurbishment. It also aims to find the best rehabilitation practices, and more sustainable solutions, which enhance the balance between environmental and economic benefits, suitable for the needs of the users. This paper identifies the aspects that should be improved and also identifies new parameters of evaluation, presenting a list of different indicators, while establishing new values for the conventional practices and best practices (benchmarks) applicable in the refurbishment of residential buildings. The final outcome of this research work is to give guidance on how to quantify the indicators of SBToolPT during a refurbishment project and also to help the residential building owners to understand the importance of implementing the principals of sustainable refurbishment.